Students' perspectives towards blended learning approach: a preliminary study in UiTM Pahang / Zuria Akmal Saad, Naliza Solat and Mohd Zulkifli Abdullah - Akmal Saad, Zuria; Solat, Naliza; Abdullah, Mohd Zulkifli (2015)
Blended learning approach uses two mediums: face-to-face interactions and knowledge through online delivery. Although a blended learning environment offers greater time flexibility for the students, there is an increasing concern for their own learning progress management. Therefore, the main objective of this study is to determine UiTM Pahang students' perspectives on blended learning. A set of questionnaire was distributed to a cluster of Bachelor in Office Systems Management (BOSM) students who have been registered in blended learning course. The data was analyzed for descriptive and correlation analysis using the SPSS Version 21. Analyzing a total of 77 responses collected from respondents, the result showed a small positive correlation between students' perspective and blended learning approach. The findings specify that the mean score for all dimensions were moderate. The findings of the present study indicated that the mean score for quality of interaction was 2.88, mean score for participation in blended learning was 3.03, mean score for quality of teaching was 3.07 and the mean score for quality of online resources was 2.92. These findings pose several implications to academicians and students. The study also paves the way for other researchers to conduct studies in similar areas especially regarding ways to enhance the effectiveness in blended learning approach. It is hoped that the findings would provide significant contributions to the areas of teaching and learning in a blended learning environment.